Hoe je provocatieve wonderverhalen kunt verstaan: Een receptie-esthetische benadering van wonderverhalen - Riemersma, N. A. (Kerk en theologie, 2025)
The miracle debate that has been at a standstill for a long time, has recently started up again. For a long time, the miracle issue has been determined by the question of the relationship between text and reality, the ‘fact or fiction’ question. In addition, the miracle question is conceived as a matter of a different understanding of reality then and now. It has caused the miracle to be considered a problematic category, which modern man does not know how to deal with. To tackle the miracle issue properly, a different way is needed. It should be seen as a matter between text and reader. Miracle stories are provocative stories. They challenge the reader to understand who alone can be held responsible for that ‘impossible’.